Influência de fatores sociais no processo decisório: experimentos no aplicativo Bike Race - Silvério, Daniel Rodrigues (2017)
Several behaviors not foreseen in the neoclassical microeconomic model are known and studied by the academy. In this dissertation, we tried to quantify effects of nonstandard decision making, especially peer effects, in the users of the Bike Race software. Two experiments were set up in the software and control and treatment groups were established. The results obtained allow us to conclude that Bike Race users have nonstandard decision making behaviors and their decisions are potentially affected by social factors. One of the experiments showed that the higher the quantity of Facebook friends, the greater the level of users’ affectation.